2008
DOI: 10.1007/s11695-008-9760-z
|View full text |Cite
|
Sign up to set email alerts
|

LapBand System® in Super-Superobese Patients (>60 kg/m2): 4-Year Results

Abstract: LAGB can be considered an appropriate bariatric surgical option in super-superobese patients both for low morbidity rate and weight loss. The end-point of BMI < 30 can be achieved with a multidisciplinary follow-up. Additional studies with more patients and longer follow-up are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
2
17
0
1
Order By: Relevance
“…In that lower BMI population, maximum weight loss was 142 lb [7], and % XSWL ranged from 38.3% to 60.8% [7][8][9]11] for laparoscopic gastric bypass and 47-69% for adjustable gastric banding [12,13]. Resolution of co-morbidities in the present study was achieved with efficacy similar to results seen elsewhere with open or laparoscopic gastric bypass [7][8][9][10][11], or gastric banding [12,13].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In that lower BMI population, maximum weight loss was 142 lb [7], and % XSWL ranged from 38.3% to 60.8% [7][8][9]11] for laparoscopic gastric bypass and 47-69% for adjustable gastric banding [12,13]. Resolution of co-morbidities in the present study was achieved with efficacy similar to results seen elsewhere with open or laparoscopic gastric bypass [7][8][9][10][11], or gastric banding [12,13].…”
Section: Discussionsupporting
confidence: 79%
“…Operative information is listed in Table 2. Medians included incision length 15 cm [12][13][14][15][16][17][18][19][20], abdominal skin-tofascia fat thickness 8 cm [5][6][7][8][9][10][11][12][13], operative time 150 min (100-210), and EBL 100 ml . ICU monitoring was used for 16 (26%), while 45 (74%) were extubated in the OR and brought to the bariatric surgical floor for telemetry monitoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toutefois, 15 ans plus tard, très peu d'études ont permis d'établir des résultats à long terme, notamment pour les patients à IMC supérieur ou égal à 50 kg/m 2 . On peut noter l'étude de G. Fielding [23] (76 patients à IMC ≥ 60 kg/m 2 avec un suivi médian de 36 mois), celle de R. Mittermair [24] (60 patients à IMC ≥ 50 kg/m 2 suivis pendant 46 mois), l'étude comparative de W. Bowne [25] (106 patients, avec bras de l'anneau gastrique ajustable, qui contient 60 patients à IMC ≥ 50 kg/m 2 avec un suivi médian de 16,2 mois) et enfin celle de F. Torchia [26] (95 patients à IMC ≥ 60 kg/m 2 avec un suivi médian de 24 mois environ). Toutes ces études concernent un nombre limité de patients et représentent un suivi qui ne va pas au-delà du moyen terme.…”
Section: Discussionunclassified
“…Weiner et al showed 53 % EWL in 28 patients at 2 years follow up [ 11 ]. Torchia has managed to show 82 % EWL at 4 years follow up with 5 patients and 69.7 % in 55 patients at 2 years follow up [ 12 ]. Proponents of banding in extreme obesity draw attention to the near absence of mortality and morbidity when compared to LRYGB or LVSG; they also claim LAGB needs shorter operating times and length of hospital stay [ 13 ].…”
Section: Laparoscopic Adjustable Gastric Band (Lagb)mentioning
confidence: 99%